1992
DOI: 10.1172/jci116079
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-induced downregulation of angiotensin II and arginine vasopressin receptors in cultured rat aortic vascular smooth muscle cells. Role of protein kinase C.

Abstract: Early diabetes mellitus is characterized by impaired responses to pressor hormones and pressor receptor downregulation. The present study examined the effect of elevated extracellular glucose concentrations on angiotensin II

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 50 publications
3
27
2
Order By: Relevance
“…This mechanism is also consistent with the failure of glucose washout over the course of an hour to significantly lower glucose-induced elevated Cai levels. A second potential mechanism for the observed glucose effects involves glucose-induced stimulation of diacylglycerol formation and protein kinase C activity (28)(29)(30), potentially recruiting calcium from intracellular storage sites via IP3 formation. The fact that glucose has similar calcium-stimulating effects in the red cell, devoid of intracellular organelles, makes this mechanism less likely.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism is also consistent with the failure of glucose washout over the course of an hour to significantly lower glucose-induced elevated Cai levels. A second potential mechanism for the observed glucose effects involves glucose-induced stimulation of diacylglycerol formation and protein kinase C activity (28)(29)(30), potentially recruiting calcium from intracellular storage sites via IP3 formation. The fact that glucose has similar calcium-stimulating effects in the red cell, devoid of intracellular organelles, makes this mechanism less likely.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to diabetes mellitus, more recent studies have shown that the PKC inhibitor staurosporine can restore to normal the previously elevated leucocyte Na+/H+ antiport activity ofdiabetic patients, thereby suggesting that diabetes-induced increases in Na+/H+ antiport activity may be dependent on PKC activation (19). Diabetes mellitus is characterized by the development of hyperglycemia, and we have recently shown that elevated extracellular glucose concentrations (20 mM) induce a sustained activation of PKC in cultured VSMC (20,21 ). Together, these observations prompt the hypothesis that metabolic factors, in particular, hyperglycemia could directly influence the activity of the Na+/H+ antiport in the vasculature ofdiabetic patients via glucose-induced activation ofPKC.…”
Section: Introductionmentioning
confidence: 92%
“…Importantly, such a reduction in the number of receptors could affect agonist-induced responses/function in cells, leading to the observed impairments of [Ca 2+ ] i responses and NO production upon bradykinin stimulation. Indeed, a 33% reduction in the number of receptors due to PKC activation induced a proportional decrease of bradykinin-mediated IP 3 formation in fibroblasts [21], and a 40% down-regulation of arginine vasopressin receptors in high-glucose-cultured vascular smooth muscle cells resulted in a similar extent of inhibition of arginine-vasopressin-induced [Ca 2+ ] i elevations [43]. Whether high glucose is also able to reduce the number of other receptors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed that acute PKC activation has a negative feedback effect on the pathway linking receptors to PLC stimulation [43,44,45]. Furthermore, PKC (especially β and δ isoforms) is excessively activated in high glucose environments due to enhanced de novo synthesis of diacylglycerol [12,32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation